Prenatally Diagnosed Aggressive Intracranial Immature Teratoma–Clinicopathological Correlation. (3rd July 2016) - Nariai, Hiroki; Price, Dana E.; Jada, Ajit; Weintraub, Lauren; Weidenheim, Karen M.; Gomes, William A.; Levy, Adam S.; Abbott, Rick; Malbari, Fatema
ABSTRACT: Objective: To describe clinicopathological correlation of congenital intracranial immature teratoma. Methods: A retrospective case analysis from a tertiary medical center. Results: We report a case of an intracranial immature teratoma detected prenatally at 35 weeks of gestation. The tumor showed rapid growth, causing acute hydrocephalus requiring subsequent ventriculoperitoneal shunting. Resective surgery was performed within 2 weeks after birth. The infant died at day of life 29. Histological examination revealed an immature teratoma, with high MIB1/Ki-67 proliferation index. Conclusion/Implications: Intracranial immature teratoma with high MIB1/Ki-67 proliferation index may serve as an independent poor prognostic factor.